Consumer attitudinal dispositions: A missing link between socio-cultural phenomenon and purchase intention of foreign products: An empirical research on young Vietnamese consumers - Nhu-Ty Nguyen (Taylor & Francis Group, 2021)
The purpose of this research is to examine the influence of consumer attitudinal dispositions on purchase intention toward foreign products and to determine which socio-cultural phenomenon are responsible for the formation of those attitudes. In this study, we employed Structural Equation Modeling (SEM) version 20 to validate the research model using data collected from 400 young Vietnamese consumers. The results reveal that cosmopolitanism and xenocentrism attitudes have positive effect on consumer preference for foreign products. Furthermore, patriotism, wordmindedness, and materialism are indicated as antecedents of consumer ethnocentrism, cosmopolitanism, and xenocentrism, respectively. The roles of consumer attitudinal dispositions are highlighted to explain the relationship between socio-cultural phenomenon and young consumers’ purchase intention. Theoretical and managerial implications for academics and practitioner addressing on consumer attitudes in Vietnamese market are also discussed.